Systematic review and meta-analysis comparing hypofractionated with conventional fraction radiotherapy in treatment of early breast cancer. (September 2015) - Zhou, Zhi-Rui; Mei, Xin; Chen, Xing-Xing; Yang, Zhao-Zhi; Hou, Jing; Zhang, Li; Yu, Xiao-Li; Guo, Xiao-Mao
Abstract Background The purpose of this meta-analysis is to evaluate the efficacy and safety of altered radiation fraction size on outcomes for early breast cancer patients. Methods A search of MEDLINE, EMBASE, WEB OF SCIENCE, Cochrane Library and ClinicalTrials.gov was conducted. Quality of the randomized controlled trials (RCTs) or non-RCTs were evaluated according to Cochrane's risk of bias tool or Methodological Index for non-Randomized Studies (MINORS). Pooled risk ratio (RR) and 95% confidence interval (CI) were calculated. Subgroup analysis was applied according to different fraction dose and sensitivity analysis was performed according to RCTs or non-RCTs. Results 23 studies were included in this systematic review. Meta-analysis demonstrated hypofractionation radiotherapy (HFRT) was associated with decreased grade 2/3 acute skin reactions compared with conventional fraction RT (CFRT), either 2.5–3.0 Gy per fraction or 5.0–6.5 Gy per fraction. HFRT with 2.5–3.0 Gy per fraction significantly decreased moderate/marked photographic changes in breast appearance compared with CFRT [RR = 0.80, 95% CI (0.70, 0.91), P = 0.001], while HFRT with more than 3.0 Gy per fraction significantly increased moderate/marked photographic changes [RR = 1.21, 95% CI (1.06, 1.38), P = 0.004]. In addition HFRT cost one-third lower than CFRT. Regarding to local regional recurrence, distant metastasis, overall survival, disease free survival, excellent/good cosmetic comes, symptomatic radiation pneumonitis, ischemic heart disease and symptomatic rib fracture, there was no significant difference between two arms. Conclusions Based on available evidence, HFRT with 2.5–3.0 Gy per fraction should be the better choice for treatment of early breast cancer patients.